Skema Visa British National Overseas dan Diplomasi Migrasi Inggris dengan Tiongkok - Ayuningtyas, Monica (Department of International Relations, Brawijaya University, 2021)
ABSTRACT In June 2020 Chinese Government officially enacted the National Security Act in Hong Kong. The UK saw the act as a serious breach of the 1997 Sino-British Joint Declaration. In response, the UK issued a new visa scheme for British National (Overseas) holders. The new scheme provides Hong Kong residents holding BNO status with a residence permit of up to 5 years and permission to apply for British citizenship. This research will describe how the UK uses migration policy in correlation to diplomacy through this phenomenon. The concept to be used is migration diplomacy by looking at aspects of the definition, categories, and objectives of the new BNO visa scheme. As a result, this research finds that the UK uses migration policy as a tool of diplomacy with China by positioning itself as a receiving country. The implementation of migration diplomacy by the UK in the BNO visa scheme aims for economic gain, related to bilateral relations with China, and promoting Global Britain.